Mechanical analysis and materials selection of a scissor lift system for pig transportation - Sanches, Lívia Valentim [UNESP]; Goulart, Celso Antonio [UNESP]; Maclean, Priscilla Ayleen Bustos [UNESP]; Villas-Bôas, Lucia Adriana [UNESP] (Universidade Estadual de Maringa, 2024)
Pigs can experience stressful moments during handling practices before arrival at the slaughter location, so adequate handling plays a crucial role in pig response to preslaughter stress. This work presents preliminary mechanical analysis and materials selection of a scissor lift system with the purpose of loading and unloading pigs for transport. The scissor lift offers a simple design and is frequently used as a lifting mechanism in the automotive, aerospace, advanced manufacturing, and transportation industries due to its flexibility to adapt to different uses. The design and mechanical analysis of the proposed scissor lift mechanism were performed to carry pigs ranging from 80 to 180 kg with a working height from 1 to 1.2 m to meet the first-floor height of traditional trucks. The model and the components of the system were dimensioned to ensure the well-being of the animals, avoid injuries, and reduce the stress that negatively affects meat quality. The structural analysis of the system was developed through classical analytical calculations in association with materials selection. The proposed design is apt to load and unload pigs safely and be used with different types of trucks.
Keywords: animal welfare; materials selection; pig transportation; scissor lift; static analysis